2014
DOI: 10.1371/journal.pone.0102792
|View full text |Cite
|
Sign up to set email alerts
|

Cycling around a Curve: The Effect of Cycling Speed on Steering and Gaze Behavior

Abstract: Although it is generally accepted that visual information guides steering, it is still unclear whether a curvature matching strategy or a ‘look where you are going’ strategy is used while steering through a curved road. The current experiment investigated to what extent the existing models for curve driving also apply to cycling around a curve, and tested the influence of cycling speed on steering and gaze behavior. Twenty-five participants were asked to cycle through a semicircular lane three consecutive time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 40 publications
4
36
1
Order By: Relevance
“…In this respect, "dwell-time fixation" is defined by a minimum fixation duration of 100 ms and a maximum visual angle variation of one degree. Consistent with protocol from similar studies [36,[42][43][44], if the visual angle varies up to one degree, it means that the gaze is fixed; the end of a fixation is defined when the eye deviates from the fixation start position by more than one degree. The list of variables measured in this study are presented in Table 1 with their description; Table 2 presents how the analysis is segmented by type of intersection and experience level.…”
Section: Analysis Approach and Indicatorsmentioning
confidence: 95%
“…In this respect, "dwell-time fixation" is defined by a minimum fixation duration of 100 ms and a maximum visual angle variation of one degree. Consistent with protocol from similar studies [36,[42][43][44], if the visual angle varies up to one degree, it means that the gaze is fixed; the end of a fixation is defined when the eye deviates from the fixation start position by more than one degree. The list of variables measured in this study are presented in Table 1 with their description; Table 2 presents how the analysis is segmented by type of intersection and experience level.…”
Section: Analysis Approach and Indicatorsmentioning
confidence: 95%
“…Consistent with this finding, in a recent study on cyclists, Vansteenkiste, Van Hamme et al (2014) found that during cycling along a circular path an anticipatory steering strategy is used at curve entrance while a compensatory closed-loop control is used during the cornering phase. The fact that a uni-phasic 4 manoeuvre can be conducted without feedback but a bi-phasic manoeuvre cannot, suggests that drivers require feedback to generate a second steering phase.…”
Section: Vehicle Steeringsupporting
confidence: 53%
“…It has been suggested that drivers may use future path and tangent point at different steering stages, for example, tangent point could be used to enter a corner whereas future path could be employed in later cornering phase (Lappi 2014). On-road experimental data also suggest that there is no evidence showing those two strategies are mutually exclusive, it is likely that drivers use multiple strategies in different situations during corner negotiation (Vansteenkiste, Van Hamme et al 2014, Itkonen, Pekkanen et al 2015.…”
Section: Vehicle Steeringmentioning
confidence: 99%
See 1 more Smart Citation
“…Otherwise, at the speed of their descent, reacting only after the effects of the irregularities on the terrain are felt would cause them to lose balance and fall. Anticipatory motor actions, thought to depend on the cerebellum (1,2), are quintessential for skilled performance in sport, but they are also part of our everyday behavior: from walking (3)(4)(5), to grasping (6)(7)(8) and to riding a bicycle (9). The question then arises as to how these actions are controlled?…”
Section: Introductionmentioning
confidence: 99%